2016
DOI: 10.1016/j.eururo.2015.12.050
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Randomized Controlled Trial of Personalized Peptide Vaccine Immunotherapy with Low-dose Dexamethasone Versus Dexamethasone Alone in Chemotherapy-naive Castration-resistant Prostate Cancer

Abstract: UMIN-CTR: 000000959.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 28 publications
2
77
0
Order By: Relevance
“…Due to its immunosuppressive effects dexamethasone is generally thought to be difficult to combine with therapeutic vaccination; however, interestingly, dexamethasone seems to increase Bcl-2 dependence in MM resulting in increased sensitivity to the Bcl-2-inhibitor venetoclax in vitro (14). Furthermore, a recent paper reported the efficacy of a peptide vaccine combined with low-dose dexamethasone in prostate cancer (15). This is interesting when considering future trials of peptide vaccinations in MM, since most MM treatments contain dexamethasone.…”
mentioning
confidence: 99%
“…Due to its immunosuppressive effects dexamethasone is generally thought to be difficult to combine with therapeutic vaccination; however, interestingly, dexamethasone seems to increase Bcl-2 dependence in MM resulting in increased sensitivity to the Bcl-2-inhibitor venetoclax in vitro (14). Furthermore, a recent paper reported the efficacy of a peptide vaccine combined with low-dose dexamethasone in prostate cancer (15). This is interesting when considering future trials of peptide vaccinations in MM, since most MM treatments contain dexamethasone.…”
mentioning
confidence: 99%
“…A series of early phase (phase I and/or phase II) clinical trials of PPV that were conducted for patients with various types of advanced cancers, including CRC, have shown the feasibility of this new approach [69][70][71][72][73][74][75][76][77][78][79][80]. For example, we have recently demonstrated that the patients treated with PPV showed a significantly longer overall survival (OS) than those with standard care and treatment in randomized phase II studies for bladder cancer and prostate cancer [72,73].…”
Section: Rationale Of Ppvmentioning
confidence: 99%
“…In a randomized phase 2 study, the combination treatment of PPV with low‐dose EMP for CRPC patients showed a longer survival than that of standard dose EMP . Another combination treatment of PPV with low‐dose dexamethasone for patients with chemotherapy‐naïve CRPC also showed longer PSA progression‐free survival and median survival time . In addition, another phase 2 study suggested that the OS of docetaxel‐resistant CRPC patients treated with PPV ( n = 20) was longer than that of historical controls ( n = 17) (17.8 months vs 10.5 months, P = 0.166) .…”
Section: Cancer Vaccinesmentioning
confidence: 99%